Non-Demented Individuals with Alzheimer’s Disease Neuropathology: Resistance to Cognitive Decline May Reveal New Treatment Strategies - Zolochevska, Olga; Taglialatela, Giulio (Current Pharmaceutical Design, 2016)
Alzheimer’s disease (AD) is a terminal neurodegenerative disorder that is characterized by accumulation of amyloid plaques and neurofibrillary tangles in the central nervous system. However, certain individuals remain cognitively intact despite manifestation of substantial plaques and tangles consistent with what would be normally associated with fully symptomatic AD. Mechanisms that allow these subjects to escape dementia remain unresolved and understanding such protective biological processes could reveal novel targets for the development of effective treatments for AD. In this review article we discuss potential compensatory mechanisms that allow these individuals to remain cognitively intact despite the typical AD neuropathology.
Keywords: resistance to cognitive decline